Effect of small donor weight and donor–recipient weight ratio on the outcome of liver transplantation in children. (27th March 2015) - Desai, Chirag S.; Sharma, Sanjay; Gruessner, Angelika; Fishbein, Thomas; Kaufman, Stuart; Khan, Khalid M.
Abstract A small donor weight is a risk factor for HAT with potential for graft loss. To test this hypothesis, we evaluated outcomes of pediatric liver transplants utilizing donors <20 kg using the UNOS database from 01/2003 to 01/2012 (n = 1311). All isolated liver transplants with whole organ grafts were included. Recipients were divided into four groups based on donor weight: group 1, donor weight <5 kg (n = 34 [2%]); group 2, 5–10 kg (431 [33%]); group 3, 10–15 kg (560 [43%]); and group 4, 15–20 kg (286 [22%]). Actuarial patient survival for the first year post‐transplant was significantly lower in groups 1 and 2 compared to groups 3 and 4 (p = 0.002), similarly the one‐yr graft function (p < 0.0001). The difference was due to graft loss within the first month for groups 1 and 2. HAT was significantly higher in groups 1 and 2 compared to others (p = 0.0006). Logistic regression analysis demonstrated donor weight as the most predictive factor with analysis of the ROC curve showing a cutoff point at 7.8 kg. The donor–recipient weight ratio did, in none of the models, gain statistical significance.